Development and Validation of Multiplex-PCR Assay for β-Carotene hydroxylase and γ-Tocopherol methyl transferase Genes Governing Enhanced Multivitamins in Maize for Its Application in Genomics-Assisted Breeding - Munegowda Manoj Gowda; Vignesh Muthusamy; Rashmi Chhabra; Hriipulou Duo; Saikat Pal; Nisrita Gain; Ashvinkumar Katral; Ravindra K. Kasana; Rajkumar U. Zunjare; Firoz Hossain (Plants)
Traditional maize possesses low concentrations of provitamin-A and vitamin-E, leading to various health concerns. Mutant alleles of crtRB1 and vte4 that enhance β-carotene (provitamin-A) and α-tocopherol (vitamin-E), respectively, in maize kernels have been explored in several biofortification programs. For genetic improvement of these target nutrients, uniplex-PCR assays are routinely used in marker-assisted selection. However, due to back-to-back breeding seasons, the time required for genotyping individually for each target gene in large backcross populations becomes a constraint for advancing the generations. Additionally, multiple PCR assays for various genes increase the required costs and resources. Here, we aimed to develop a multiplex-PCR assay to simultaneously identify different allelic forms of crtRB1 and vte4 genes and validate them in a backcross-based segregating population. The PCR assay was carried out using newly developed primers for crtRB1 and a gene-specific primer for vte4. The uniplex-PCR assay was standardized for selected primer pairs in the BC1F1 population segregating for crtRB1 and vte4 genes. Subsequently, a multiplex-PCR assay for crtRB1 and vte4 genes was developed and employed for genotyping in the BC1F1 population. The assay differentiated among four possible genotypic classes, namely crtRB1+crtRB1/vte4+vte4, crtRB1crtRB1/vte4+vte4, crtRB1+crtRB1/vte4+vte4+, and crtRB1crtRB1/vte4+vte4+. This newly developed multiplex-PCR assay saved 41.7% of the cost and 35.6% of the time compared to two individual uniplex-PCR assays. The developed assay could accelerate maize nutritional quality breeding programs through rapid and cost-effective genotyping for the target genes. This is the first report of a multiplex-PCR assay specific to crtRB1 and vte4 genes for its use in genomics-assisted breeding in maize.